Utility Regulators : Supporting Nascent Institutions in the Developing World - Gray, Philip (World Bank, Washington, DC, 2012)
The wave of infrastructure privatization sweeping the world over the past decade or so has given rise to a new category of professional - the specialist utility regulator. These regulators, charged with administering regulatory frameworks that seek to balance the interests of consumers and investors in technically complex and politically sensitive industries, can have a major impact on the performance of privatized firms, on the cost of investment capital (and thus on infrastructure tariffs), and on the sustainability of reforms. For this reason the development of professional, capable utility regulators should be a key part of reform efforts. While new regulators in any country can expect to face many difficulties, the challenges are particularly daunting for regulators in developing countries. This Note reviews those challenges and presents some of the main strategies for supporting new utility regulators in the developing world.